Anxiety is associated with cognitive impairment in newly-diagnosed Parkinson's disease. (March 2017) - Dissanayaka, Nadeeka N.W.; Lawson, Rachael A.; Yarnall, Alison J.; Duncan, Gordon W.; Breen, David P.; Khoo, Tien K.; Barker, Roger A.; Burn, David J.; ,
Abstract: Introduction: Anxiety and mild cognitive impairment (MCI) are prevalent non-motor manifestations of Parkinson's disease (PD). While few studies have demonstrated a possible link between cognitive dysfunction and anxiety in PD, to our knowledge, no studies have directly examined the association between them. This study investigated the association between anxiety and cognitive deficits in newly diagnosed PD patients. Methods: Patients with newly diagnosed PD (N = 185) were recruited from community and outpatient clinics. Anxiety was assessed using the Unified Parkinson's Disease Rating Scale (MDS-UPDRS) clinician rated anxiety item, which has previously been validated against a standardized criteria for the diagnosis of anxiety disorders in PD. Participants scoring ≥2 were classified as anxious. A threshold of 1 SD below normative values (obtained from controls) was used to define cognitive impairment. Impairments in specific cognitive domains were identified as being >1 SD below controls in ≥1 test per domain. Results: After controlling for age, education and motor severity, patients with anxiety were three times more likely to have cognitive impairment compared to those without anxiety (OR = 3.0, 95% CI = 1.2–7.3, p < 0.05). Patients with anxiety were more than twice as likely to be classified as having cognitive impairment due to impairment in the memory domain compared with PD without anxiety (OR = 2.3, 95% CI = 1.0–5.1, p < 0.05), whilst no associations were found between anxiety and performance on other cognitive domains. Conclusion: This study shows an association between anxiety and cognitive impairment (specifically memory impairment). Examining the neural basis of this association warrants future research in this developing field. Highlights: Anxiety was associated with mild cognitive impairment (MCI) in PD. Patients with anxiety were three times more likely to have cognitive impairment. Anxiety was specifically associated with impairments in the memory domain.